PERAN PROFITABILITAS SEBAGAI PEMODERASI DETERMINAN FINANCIAL DISTRESS PERUSAHAAN PERTAMBANGAN - Widhiastuti, Ni Luh Putu; Pradnyani, I Gusti Agung Arista (Faculty of Economics and Business University of Mataram, 2024)
This study aims to analyze the role of profitability during financial distress on the relationship between size, sales growth, leverage, liquidity, and operational capacity. With a purposive sampling approach, testing was conducted on 63 mining business companies on the IDX in 2020 and 2022. Data were analyzed using moderation data analysis (MRA). The study's results indicate that operational capacity and liquidity reduce financial distress. Leverage and company size have a detrimental impact on financial distress, but increased sales do not affect financial distress. Other research results show that profitability cannot control the relationship between leverage and liquidity during economic crises. Profitability is proven to moderate the relationship between operational capacity, sales growth, and company size during the financial crisis. This study implies that it is essential to recognize the possibility of financial distress early on to save the company from bankruptcy.